Medical imaging technologies applied to the COVID-19 context - Yago Viana Pinto; Rodrigo Modesto Gadelha Gontijo; Andréa Vidal Ferreira (Brazilian Journal of Radiation Sciences, 2022)
Since the outbreak of COVID-19 disease, imaging methods such as X-Ray and Computed Tomography have stood out as feasible tools for diagnosing and evaluating the disease, especially regarding its lung occurrence in symptomatic patients. However, in the course of the pandemic, COVID-19 showed its effects in other tissues such as heart, brain and veins, triggering inflammatory processes. Thus, other imaging methods such as Positron Emission Tomography-Computer Tomography (PET-CT) and Magnetic Resonance have shown to be good sources of information about the location and intensity of the inflammation. This article reviews some of these imaging methods, its findings, feasibilities, advantages and limitations for COVID-19 diagnostic and evaluating.